2009
DOI: 10.1017/s1368980009992199
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mineral density of adolescent mothers during the 12-month postpartum period

Abstract: Objective: Bone mineral density (BMD) loss has been described in adult women in the 12-month postpartum period. However, little is known about the precise BMD pattern in adolescent mothers. The present study aimed to evaluate BMD in Argentinean adolescent mothers followed up during the 12-month postpartum period. Design: Analytical, prospective clinical trial. BMD and body composition were determined by dual-energy X-ray absorptiometry; bone mineral content (BMC) and BMD were measured in the lumbar spine (L2-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
3
6
0
4
Order By: Relevance
“…Therefore, it was not possible to establish a new PTWI that could be considered "protective" of health. 16 Childhood lead exposure in our population was recently estimated at a relatively low median blood lead level of 2.2 µg/dL, 12 and no specific sources of exposure were identified, so the dietary contribution to lead burden could be relevant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, it was not possible to establish a new PTWI that could be considered "protective" of health. 16 Childhood lead exposure in our population was recently estimated at a relatively low median blood lead level of 2.2 µg/dL, 12 and no specific sources of exposure were identified, so the dietary contribution to lead burden could be relevant.…”
Section: Discussionmentioning
confidence: 90%
“…According to the European Food Safety Authority (EFSA), the food groups that contributed the most to lead exposure in the European population included bread, toasts, soups, vegetables, fruits, water, nonalcoholic beverages, alcoholic beverages, sugar and confectionery. 16 In total diet surveys conducted in the USA between 1991 and 2005, the foods with the highest lead intake included sweet cucumber pickles, milk chocolate candy bars, canned fruit cocktail, chocolate syrup, canned potatoes, canned apricots, and shrimps. 16 In the SCOOP study, conducted in 2004 in 10 European countries, the highest lead levels were found in herbs and spices, followed by game meat, dietetic food, food supplements, and wine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, se investigó la marca de los alimentos consumidos y dónde la familia realizaba las compras de alimentos frescos y secos. La encuesta alimentaria fue diseñada sobre la base de estudios previos realizados en la Institución 14,15 y realizada por licenciados en Nutrición. Etapa 2.…”
Section: Etapas Del Estudio Etapa 1 Encuesta Alimentariaunclassified
“…34 Sabe-se que, na lactação, a mobilização do cálcio ósseo é um dos principais mecanismos de adaptação materna à elevada demanda de cálcio para a produção do leite. 35 No entanto, em mães adolescentes, perdas ósseas de maior magnitude ao reportado em adultas 36 têm sido observadas, 33,34,37,38 especialmente naquelas com baixa ingestão dietética de cálcio (500-895 mg/dia). 34,37,38 Em adolescentes, a recuperação da massa óssea após o desmame é controversa.…”
Section: Condições Fisiológicas Associadasimpacto Da Gestação E Lactaunclassified